The Relationship Between Husband Support And Antenatal Care Compliance In Pregnant Women At The Puskesmas Tanjung Selamat, Langkat District, 2022. - Sumiatik Sumiatik (Sean Institute, 2023)
Antenatal Care is one of the health services to monitor the progress of the pregnancy process in order to ensure the health of the mother and the growth and development of the fetus in it, find out about pregnancy complications that may occur during early pregnancy, including a history of illness and surgery. This study aims to determine the relationship between husband's support and antenatal care compliance for pregnant women at the Tanjung Selamat Health Center, Padang Tualang District.This research method uses a quantitative descriptive approach. The research data was taken from information on pregnant women as many as 40 respondents. Data was collected by distributing questionnaires in the form of questions given to respondents to obtain information.The results showed that the number of respondents who received support from their husbands did antenatal care 26 respondents (65.00%) there were 24 respondents (77.42%) who obeyed the pregnancy examination, and 2 respondents (22.23%). disobedient. Meanwhile, 14 respondents (35.00%) did not receive husband's support, 7 respondents (22.58%) complied with antenatal care and 7 respondents (77.77%) did not comply. In this study, there was a relationship between husband's support and antenatal care compliance as evidenced by the results of the Chi-Square statistical test, it was found that the value of ρ value = 0.002 < α = 0.05 where H0 was rejected and Ha was accepted. Suggestions in this study inform that the importance of prenatal care (Antenatal Care) so that husbands are expected to provide support, especially assessment support, instrumental support, and emotional support as well as motivation to wives to do pregnancy checks.